Carbon-doped non-noble metal high-entropy alloy hydrogen evolution catalytic electrode and preparation method thereof

Preparation of carbon doping of non -precious metal high -entropy alloy hydrogen catalytic electrodes through powder metallurgical methods, solving the problem of high preparation costs, complex processes and low catalytic activity in existing technology, and realized the effects of simple craftsmanship, low cost and high catalytic activity. Applicable to electrolytic hydrogen hydrogen hydrogen in industrialized production and alkaline environments.

CN119372705APending Publication Date: 2025-01-28SOUTHWEST JIAOTONG UNIV

Patent Information

Application Number
CN202411576915.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing hydrogen evolution catalytic electrode has high preparation cost, complex production process and low catalytic activity, making it difficult to meet the needs of industrial production.

Method used

Powder metallurgical methods are used to prepare carbon doping doped non-precious metal high-entropy alloy alloy hydrogen analysis of hydrogen catalytic electrodes. Through ball grinding and non-pressure sintering processes, simplifying the process process, reducing costs, and using carbon to form a transition metal carbide-carbonized molybdenum coordinated effect to improve catalytic catalytic catalytic active.

Benefits of technology

The hydrogen analysis electrode with simple craftsmanship, low cost, and high catalytic activity is suitable for the catalytic reactions of electrolytic hydrogen hydrogen hydrogen hydrogen hydrogen in alkaline environments, which improves the efficiency of hydrogen making and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372705A_ABST
    Figure CN119372705A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-doped non-noble metal high-entropy alloy hydrogen evolution catalytic electrode and a preparation method thereof, and belongs to the technical field of water electrolysis hydrogen production. The preparation method comprises the following steps: (1) blending four metal powder of Fe, Co, Ni and Mo with carbon powder, ball-milling, standing and passivating to obtain mixed powder; and (2) carrying out compression molding on the mixed powder obtained in the step (1), and sintering. The preparation method is simple in process, the hydrogen evolution catalytic electrode can be obtained only through two steps of mechanical alloying and pressureless sintering, operation is easy and convenient, large-scale preparation can be achieved, and industrialization is easy; through a carbon doping mode, a transition metal carbide-molybdenum carbide and quaternary high-entropy alloy synergistic effect is formed in the electrode material, the free energy of a hydrogen intermediate is obviously reduced, the mass transfer process in electrochemical reaction is facilitated, and the electrode material has excellent hydrogen evolution catalytic performance and is suitable for water electrolysis hydrogen evolution catalytic reaction in an alkaline environment; the hydrogen production efficiency can be improved, and the energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a carbon-doped non-precious metal high-entropy alloy hydrogen evolution catalytic electrode and a preparation method thereof. Background Art

[0002] As energy is depleted, hydrogen has great potential as a renewable clean energy source, and water electrolysis is considered to be a clean and efficient means of hydrogen production. However, the current method of hydrogen production through proton exchange membranes is still highly dependent on precious metal-based catalysts. A series of precious metal catalysts, such as platinum and palladium, are excellent representatives of hydrogen evolution reaction catalysts. However, catalysts composed of precious metal elements have the disadvantages of scarce resources and high costs, which limit their practical applications. In this context, the development of alternative, low-cost, and highly active non-precious metal hydrogen evolution catalysts has become a necessary trend.

[0003] In response to the above problems, researchers have found that transition metal-based catalysts (TMEs) are considered to be a good choice to replace precious metal-based catalysts. However, in practical applications, binary transition metal alloys are very limited in regulating the free energy of hydrogen adsorption during water electrolysis due to their composition and fixed stoichiometric ratio, which greatly limits the increasingly stringent performance improvement requirements. Therefore, expanding the elements of transition metal alloys and doping non-metallic elements to form transition metal compounds are considered to be effective solutions to the above problems. In recent years, transition metal phosphides (TMPs), transition metal nitrides (TMNs), transition metal chalcogenides (TMDs), and transition metal carbides (TMCs) have been widely studied. However, these transition metal compounds have limited room for improving catalyst performance, and the composition changes are diverse and difficult to control, which limits large-scale industrial production.

[0004] In the invention with publication number CN105483744A, Soochow University invented a porous hydrogen evolution catalyst and its preparation method, using ultrasonic electrodeposition to obtain a copper sheet plated with Co and W elements in a plating solution containing the elements Co and W; and then heat-preserving it in a protective atmosphere mixed with hydrogen and argon for a certain period of time to obtain a porous structure hydrogen evolution catalytic electrode. The electrode described in this method is 1 mol·L -1 In the KO H solution, the hydrogen evolution current density is 250 mA cm -2 The overpotential (η250) of hydrogen evolution is 0.288-0.387V, and the current decay rate of continuous electrolysis of hydrogen evolution for 48 hours under the constant potential condition of 1.5V vs. SCE is 6.28%-8.21%. However, the preparation process of the catalytic electrode of this invention is long, with many processes, and more raw materials are needed before ultrasonic electrodeposition. The process is relatively complicated and the equipment used is not suitable for large-scale industrial production.

[0005] In the invention with publication number CN117552031A, a phosphorus-doped hydrogen evolution catalytic electrode was invented. Phosphorus was introduced into a multi-element alloy material containing nickel, copper and vanadium by a one-step electrodeposition method, thereby achieving cathodic protection for the active electrode, avoiding its oxidative deactivation in a strong alkaline environment, and enhancing the stability of the catalyst. However, in this invention, the substrate needs to be pre-treated in advance, the process is long, more equipment is used, and the electroplating solution needs to be compounded with multiple solutions. The process is cumbersome and not suitable for industrial production.

[0006] In summary, there is an urgent need to develop a transition metal-based catalyst that is low in cost, simple to operate, suitable for industrial production and has high catalytic activity. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode and a preparation method thereof, so as to solve the problems of high preparation cost, complex production process and low catalytic activity of existing hydrogen evolution catalytic electrodes.

[0008] The technical solution of the present invention to solve the above technical problems is as follows:

[0009] A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode comprises the following steps:

[0010] (1) Four metal powders of Fe, Co, Ni and Mo are mixed with carbon powder, ball milled, and allowed to stand for passivation to obtain a mixed powder;

[0011] (2) Pressing the mixed powder obtained in step (1) into a shape and sintering the mixture to obtain a product.

[0012] The beneficial effects of the present invention are as follows: the present invention prepares a carbon-doped multi-element alloy electrode with simple process, low cost and high catalytic activity by powder metallurgy. The catalytic efficiency is significantly improved in an alkaline environment, the mechanical alloying method successfully dopes carbon into the quaternary alloy, and the quaternary alloy and transition metal carbide synergistically reduce the free energy of hydrogen intermediates; the pressureless sintering method enables the electrode to have a porous self-supporting structure that can provide more active surface area.

[0013] Furthermore, in step (1), the atomic percentages of the four metal powders of Fe, Co, Ni and Mo are: Fe 10-20%, Co 25-28%, Ni 35-45% and Mo 20-22%; and the particle size of the four metal powders is 60-65 μm.

[0014] Furthermore, the atomic percentages of the four metal powders of Fe, Co, Ni and Mo are: Fe 10%, Co 25%, Ni 45% and Mo 20%.

[0015] Furthermore, in step (1), the mass ratio of the total mass of the four metal powders to the carbon powder is (50-70):(0.05-0.2), and the particle size of the carbon powder is 60-65 μm.

[0016] Preferably, in step (1), the mass ratio of the total mass of the four metal powders to the carbon powder is 60:0.1, and the particle size of the carbon powder is 63 μm.

[0017] Furthermore, the ball milling conditions in step (1) are as follows: the ball-to-material mass ratio is (5-20): (0.8-1.2), and stearic acid is added in an amount of 0.8-1.2% of the total mass of the four metal powders; the mixture is pre-mixed at a speed of 230-270 rpm for 5-7 hours, and then mechanically alloyed and mixed at a speed of 280-320 rpm for 80-90 hours; and the mechanical alloying mixing is performed by interval ball milling, with each ball milling for 40-60 minutes with an interval of 5-15 minutes.

[0018] Preferably, the ball milling conditions in step (1) are as follows: the ball-to-material mass ratio is 10:1, and stearic acid is added in an amount of 1% of the total mass of the four metal powders; premixing is performed at a speed of 250 rpm for 6 hours, and then mechanical alloying mixing is performed at a speed of 300 rpm for 84 hours; mechanical alloying mixing is performed by interval ball milling, with an interval of 10 minutes for each 50 minutes of ball milling.

[0019] The beneficial effect of adopting the above further technical solution is that the present invention prevents metal powder from sticking and cold welding by adding stearic acid as a process control agent.

[0020] Furthermore, the static passivation time in step (1) is 48 hours.

[0021] Furthermore, the conditions for the pressing molding in step (2) are: first pressing in a mold to obtain a disc-shaped green body, and then applying a single-sided pressure of 5-7 MPa for 5-20 minutes; the diameter of the disc-shaped green body is 5-20 mm and the thickness is 1-3 mm.

[0022] Preferably, the conditions for the pressing in step (2) are: first pressing in a mold to obtain a disc-shaped body, and then applying a single-sided pressure of 6 MPa for 10 minutes; the diameter of the disc-shaped body is 10 mm and the thickness is 2 mm.

[0023] Furthermore, the sintering conditions in step (2) are: in a protective gas atmosphere, first heating the temperature to 200-250°C at a heating rate of 8-12°C / min and keeping it warm for 40-80min, then heating the temperature to 1050-1150°C at a heating rate of 4-6°C / min and keeping it warm for 40-80min.

[0024] Preferably, the sintering conditions in step (2) are: in a protective gas atmosphere, first heating to 232° C. at a heating rate of 10° C. / min and keeping warm for 60 min, then heating to 1100° C. at a heating rate of 5° C. / min and keeping warm for 60 min.

[0025] A carbon-doped non-noble metal high entropy alloy hydrogen evolution catalytic electrode is prepared by adopting the preparation method.

[0026] The application of the above-mentioned carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode in hydrogen production by electrolysis.

[0027] The present invention has the following beneficial effects:

[0028] (1) The powder metallurgy method used in the present invention is simple in process and only requires two steps, mechanical alloying and pressureless sintering, to obtain the hydrogen evolution catalytic electrode. Mechanical alloying introduces carbon into the iron-cobalt-nickel-molybdenum quaternary alloy, and the pressureless sintering method enables the electrode to form a porous self-supporting structure.

[0029] (2) The present invention has low cost, does not use precious metal elements as raw materials, is easy to operate, can be prepared on a large scale, and is easy to industrialize;

[0030] (3) The present invention forms a synergistic effect of transition metal carbide-molybdenum carbide and quaternary high entropy alloy in the electrode material by carbon doping, which significantly reduces the free energy of hydrogen intermediates and is beneficial to the mass transfer process in the electrochemical reaction;

[0031] (4) The present invention has excellent hydrogen evolution catalytic performance and is suitable for the catalytic reaction of hydrogen evolution by electrolysis of water in an alkaline environment, which can improve hydrogen production efficiency and reduce energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a 1 μm scale SEM image of the carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode prepared in Example 1-4;

[0033] Figure 2 The SEM images of the carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrodes prepared in Example 2 and Comparative Examples 1-2 at a scale of 10 μm;

[0034] Figure 3 The LSV, Tafel and EIS electrochemical performances of the carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode prepared in Examples 1-4 in 1.0 KOH solution;

[0035] Figure 4 The LSV, Tafel and EIS electrochemical properties of the carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrodes prepared in Example 2 and Comparative Examples 1-2 in 1.0KOH solution;

[0036] Figure 5 This is the EDX spectrum of the carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode prepared in Example 2 at a scale of 1 μm. DETAILED DESCRIPTION

[0037] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0038] Embodiment 1:

[0039] A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode comprises the following steps:

[0040] (1) Premixed powder

[0041] Dry Fe, Co, Ni and Mo four metal element powders are mixed according to Fe 20 Co 25 Ni 35 Mo 20 The total mass is 60g, and 0.1g of carbon powder is weighed as a carbon source. The powder particle size is about 63μm and the purity is 99.8%. The mixture is loaded into a high-energy planetary ball mill and premixed at 250rpm for 6h. The ball-to-material mass ratio in the planetary ball mill is 10:1, and 0.6g of high-grade pure stearic acid is added as a process control agent to prevent metal powder from sticking and cold welding. Ar gas is filled in the ball mill as a protective atmosphere.

[0042] (2) Mechanical alloying

[0043] After the premixing, the rotation speed was adjusted to 300 rpm for 84 hours of mechanical alloying, using an interval ball milling method with a 10-minute interval every 50 minutes. After the ball milling was completed, it was placed in the air for passivation for 48 hours.

[0044] (3) Green body pressing

[0045] Take 5g of the mechanically alloyed powder and pour it into a graphite mold, place it on a manual tablet press and entropy press it into a disc-shaped green body with a diameter of 10mm and a thickness of 2mm. Then, a single-sided pressure of 6MPa is applied and the pressure is maintained for 10min to ensure the compaction of the powder and release the residual stress in the green body.

[0046] (4) Pressureless sintering

[0047] The pressed green body was placed in a corundum crucible boat and sent into a tubular furnace with flowing argon atmosphere for sintering. Before sintering, 200 mL / min of argon was continuously introduced to ensure that the air in the tubular furnace was quickly discharged to avoid contamination of the green body by impurities. The sintering heating program was set as follows: first, the temperature was increased to 232°C at a heating rate of 10°C / min and kept for 60 minutes, then the temperature was increased to 1100°C at a heating rate of 5°C / min and kept for 60 minutes, and finally, argon was continuously introduced until it dropped to room temperature to obtain a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode.

[0048] Embodiment 2:

[0049] A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode comprises the following steps:

[0050] (1) Premixed powder

[0051] Dry Fe, Co, Ni and Mo four metal element powders are mixed according to Fe 10 Co 25 Ni 45 Mo 20 The total mass is 60g, and 0.1g of carbon powder is weighed as a carbon source. The powder particle size is about 63μm and the purity is 99.8%. The mixture is loaded into a high-energy planetary ball mill and premixed at 250rpm for 6h. The ball-to-material mass ratio in the planetary ball mill is 10:1, and 0.6g of high-grade pure stearic acid is added as a process control agent to prevent metal powder from sticking and cold welding. Ar gas is filled in the ball mill as a protective atmosphere.

[0052] (2) Mechanical alloying

[0053] After the premixing, the rotation speed was adjusted to 300 rpm for 84 hours of mechanical alloying, using an interval ball milling method with a 10-minute interval every 50 minutes. After the ball milling was completed, it was placed in the air for passivation for 48 hours.

[0054] (3) Green body pressing

[0055] Take 5g of the mechanically alloyed powder and pour it into a graphite mold, place it on a manual tablet press and entropy press it into a disc-shaped green body with a diameter of 10mm and a thickness of 2mm. Then, a single-sided pressure of 6MPa is applied and the pressure is maintained for 10min to ensure the compaction of the powder and release the residual stress in the green body.

[0056] (4) Pressureless sintering

[0057] The pressed green body was placed in a corundum crucible boat and sent into a tubular furnace with flowing argon atmosphere for sintering. Before sintering, 200 mL / min of argon was continuously introduced to ensure that the air in the tubular furnace was quickly discharged to avoid contamination of the green body by impurities. The sintering heating program was set as follows: first, the temperature was increased to 232°C at a heating rate of 10°C / min and kept for 60 minutes, then the temperature was increased to 1100°C at a heating rate of 5°C / min and kept for 60 minutes, and finally, argon was continuously introduced until it dropped to room temperature to obtain a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode.

[0058] Embodiment 3:

[0059] A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode comprises the following steps:

[0060] (1) Premixed powder

[0061] Dry Fe, Co, Ni and Mo four metal element powders are mixed according to Fe 15 Co 25 Ni 40 Mo 20 The total mass is 60g, and 0.1g of carbon powder is weighed as a carbon source. The powder particle size is about 63μm and the purity is 99.8%. The mixture is loaded into a high-energy planetary ball mill and premixed at 250rpm for 6h. The ball-to-material mass ratio in the planetary ball mill is 10:1, and 0.6g of high-grade pure stearic acid is added as a process control agent to prevent metal powder from sticking and cold welding. Ar gas is filled in the ball mill as a protective atmosphere.

[0062] (2) Mechanical alloying

[0063] After the premixing, the rotation speed was adjusted to 300 rpm for 84 hours of mechanical alloying, using an interval ball milling method with a 10-minute interval every 50 minutes. After the ball milling was completed, it was placed in the air for passivation for 48 hours.

[0064] (3) Green body pressing

[0065] Take 5g of the mechanically alloyed powder and pour it into a graphite mold, place it on a manual tablet press and entropy press it into a disc-shaped green body with a diameter of 10mm and a thickness of 2mm. Then, a single-sided pressure of 6MPa is applied and the pressure is maintained for 10min to ensure the compaction of the powder and release the residual stress in the green body.

[0066] (4) Pressureless sintering

[0067] The pressed green body was placed in a corundum crucible boat and sent into a tubular furnace with flowing argon atmosphere for sintering. Before sintering, 200 mL / min of argon was continuously introduced to ensure that the air in the tubular furnace was quickly discharged to avoid contamination of the green body by impurities. The sintering heating program was set as follows: first, the temperature was increased to 232°C at a heating rate of 10°C / min and kept for 60 minutes, then the temperature was increased to 1100°C at a heating rate of 5°C / min and kept for 60 minutes, and finally, argon was continuously introduced until it dropped to room temperature to obtain a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode.

[0068] Embodiment 4:

[0069] A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode comprises the following steps:

[0070] (1) Premixed powder

[0071] Dry Fe, Co, Ni and Mo four metal element powders are mixed according to Fe 11 Co 28 Ni 39 Mo 22 The total mass is 60g, and 0.1g of carbon powder is weighed as a carbon source. The powder particle size is about 63μm and the purity is 99.8%. The mixture is loaded into a high-energy planetary ball mill and premixed at 250rpm for 6h. The ball-to-material mass ratio in the planetary ball mill is 10:1, and 0.6g of high-grade pure stearic acid is added as a process control agent to prevent metal powder from sticking and cold welding. Ar gas is filled in the ball mill as a protective atmosphere.

[0072] (2) Mechanical alloying

[0073] After the premixing, the rotation speed was adjusted to 300 rpm for 84 hours of mechanical alloying, using an interval ball milling method with a 10-minute interval every 50 minutes. After the ball milling was completed, it was placed in the air for passivation for 48 hours.

[0074] (3) Green body pressing

[0075] Take 5g of the mechanically alloyed powder and pour it into a graphite mold, place it on a manual tablet press and entropy press it into a disc-shaped green body with a diameter of 10mm and a thickness of 2mm. Then, a single-sided pressure of 6MPa is applied and the pressure is maintained for 10min to ensure the compaction of the powder and release the residual stress in the green body.

[0076] (4) Pressureless sintering

[0077] The pressed green body was placed in a corundum crucible boat and sent into a tubular furnace with flowing argon atmosphere for sintering. Before sintering, 200 mL / min of argon was continuously introduced to ensure that the air in the tubular furnace was quickly discharged to avoid contamination of the green body by impurities. The sintering heating program was set as follows: first, the temperature was increased to 232°C at a heating rate of 10°C / min and kept for 60 minutes, then the temperature was increased to 1100°C at a heating rate of 5°C / min and kept for 60 minutes, and finally, argon was continuously introduced until it dropped to room temperature to obtain a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode.

[0078] Comparative Example 1:

[0079] A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode comprises the following steps:

[0080] (1) Premixed powder

[0081] Dry Fe, Co, Ni and Mo four metal element powders are mixed according to Fe 10 Co 25 Ni 45 Mo 20 The total mass is 60g, and 0.1g of carbon powder is weighed as a carbon source. The powder particle size is about 63μm and the purity is 99.8%. The mixture is loaded into a high-energy planetary ball mill and premixed at 250rpm for 6h. The ball-to-material mass ratio in the planetary ball mill is 10:1, and 0.6g of high-grade pure stearic acid is added as a process control agent to prevent metal powder from sticking and cold welding. Ar gas is filled in the ball mill as a protective atmosphere.

[0082] (2) Mechanical alloying

[0083] After the premixing, the rotation speed was adjusted to 300 rpm for 84 hours of mechanical alloying, using an interval ball milling method with a 10-minute interval every 50 minutes. After the ball milling was completed, it was placed in the air for passivation for 48 hours.

[0084] (3) Green body pressing

[0085] Take 5g of the mechanically alloyed powder and pour it into a graphite mold, place it on a manual tablet press and entropy press it into a disc-shaped green body with a diameter of 10mm and a thickness of 2mm. Then, a single-sided pressure of 6MPa is applied and the pressure is maintained for 10min to ensure the compaction of the powder and release the residual stress in the green body.

[0086] (4) Pressureless sintering

[0087] The pressed green body was placed in a corundum crucible boat and sent into a tubular furnace with flowing argon atmosphere for sintering. Before sintering, 200 mL / min of argon was continuously introduced to ensure that the air in the tubular furnace was quickly discharged to avoid contamination of the green body by impurities. The sintering heating program was set as follows: first, the temperature was increased to 232°C at a heating rate of 10°C / min and kept for 60 minutes, then the temperature was increased to 900°C at a heating rate of 5°C / min and kept for 60 minutes, and finally, argon was continuously introduced until it dropped to room temperature to obtain a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode.

[0088] Comparative Example 2:

[0089] A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode comprises the following steps:

[0090] (1) Premixed powder

[0091] Dry Fe, Co, Ni and Mo four metal element powders are mixed according to Fe 10 Co 25 Ni 45 Mo 20 The total mass is 60g, and 0.1g of carbon powder is weighed as a carbon source. The powder particle size is about 63μm and the purity is 99.8%. The mixture is loaded into a high-energy planetary ball mill and premixed at 250rpm for 6h. The ball-to-material mass ratio in the planetary ball mill is 10:1, and 0.6g of high-grade pure stearic acid is added as a process control agent to prevent metal powder from sticking and cold welding. Ar gas is filled in the ball mill as a protective atmosphere.

[0092] (2) Mechanical alloying

[0093] After the premixing, the rotation speed was adjusted to 300 rpm for 84 hours of mechanical alloying, using an interval ball milling method with a 10-minute interval every 50 minutes. After the ball milling was completed, it was placed in the air for passivation for 48 hours.

[0094] (3) Green body pressing

[0095] Take 5g of the mechanically alloyed powder and pour it into a graphite mold, place it on a manual tablet press and entropy press it into a disc-shaped green body with a diameter of 10mm and a thickness of 2mm. Then, a single-sided pressure of 6MPa is applied and the pressure is maintained for 10min to ensure the compaction of the powder and release the residual stress in the green body.

[0096] (4) Pressureless sintering

[0097] The pressed green body was placed in a corundum crucible boat and sent into a tubular furnace with flowing argon atmosphere for sintering. Before sintering, 200 mL / min of argon was continuously introduced to ensure that the air in the tubular furnace was quickly discharged to avoid contamination of the green body by impurities. The sintering heating program was set as follows: first, the temperature was increased to 232°C at a heating rate of 10°C / min and kept for 60 minutes, then the temperature was increased to 1000°C at a heating rate of 5°C / min and kept for 60 minutes, and finally, argon was continuously introduced until it dropped to room temperature to obtain a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode.

[0098] Test Example 1:

[0099] The carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode prepared in Example 1-4 was observed by scanning electron microscope. The experimental results are as follows: Figure 1 and Figure 2 shown.

[0100] Figure 1 The results show that at the same sintering temperature of 1100°C, irregular holes are formed on the surface of the electrodes prepared under the four groups of different compositions, and the gray matrix melts more evenly, with white granular precipitates. Among them, the electrode prepared in Example 2 has more holes and white granular precipitates, and the pore structure and precipitates are evenly distributed. This pore structure can significantly increase the number of active sites and their feasibility, increase the specific surface area, optimize the adsorption and desorption of reactants, and improve mass transfer, thereby having better electrocatalytic activity.

[0101] Figure 2 The results show that the surface morphology of the electrode prepared in Comparative Example 1 shows a large number of lamellar structures, and no precipitates appear, while the lamellar structures on the surface of the electrode prepared in Comparative Example 2 are relatively reduced, and a relatively uniform molten matrix appears, but there is still no obvious precipitate as in the embodiment. Compared with the electrode surface prepared in Example 2 of the present invention, the lamellar structure completely disappears, and it can be seen that a uniform molten matrix is ​​formed, corresponding to the FCC matrix phase in the XRD spectrum, and the formed surface has a large number of pore structures, and obvious granular precipitates can be seen on the surface of the matrix and in the pores. Compared with Comparative Examples 1 and 2, the electrode prepared in Example 2 provides more active sites through the formation of pores and new phases in the matrix, which significantly improves the electrocatalytic activity of the catalyst.

[0102] Test Example 2:

[0103] The hydrogen evolution catalytic electrodes prepared in Examples 1-4 and Comparative Examples 1-2 of the present invention were tested for their hydrogen evolution catalytic performance in a 1.0 mol / L KOH solution using an electrochemical workstation with a three-electrode system. The reference electrode used in the three-electrode system was Hg / HgO, the counter electrode was a stone mill rod, and the working electrode should be parallel to the counter electrode to ensure the maximum test surface. The sample activation treatment was performed by continuous CV scanning in the range of 25-100V, the purpose of which was to eliminate impurities on the catalyst surface and expose more active sites, and then the electrochemical test could be performed after reaching a steady state.

[0104] The experimental results are as follows Figure 3 and Figure 4 shown.

[0105] Figure 3 The results show that the overall electrocatalytic performance of the electrodes prepared in the four examples of the present invention shows a trend of Example 2> Example 1> Example 4> Example 3. At the same sintering temperature, Example 2 has a lower overpotential than other examples, 10 mA·cm -2 The current density is only 76 mV, and the Tafel slope is only 56 mV / dec, which corresponds to the Volmer reaction in the decisive reaction step of HER.

[0106] Figure 4 The results show that compared with the electrodes prepared in Comparative Examples 1, 2 and Example 2, the electrochemical performance of Example 2 is significantly better than that of Comparative Examples 1 and 2, and the electrochemical performance of Comparative Example 2 is better than that of Comparative Example 1. At 1100°C, non-metallic elements induce strong charge transfer and produce s, pd hybridization with the main metal to form a new phase Mo2C. Due to the strong non-metal-metal bond, protons can more easily pass through the barrier, helping the dissociation and desorption of hydrogen. This is one of the reasons why the electrochemical performance of Example 2 is significantly better than that of Comparative Examples 1 and 2. At the same time, as the temperature rises, the alloy begins to melt to form an FCC matrix, and Mo2C precipitates from the matrix to form a porous self-supporting structure, providing more active sites. This is also one of the reasons why the electrochemical performance of Example 2 is significantly better than that of Comparative Examples 1 and 2.

[0107] Test Example 3:

[0108] The electrode material prepared in Example 2 was scanned using an X-ray energy spectrum (EDX) to analyze the distribution of each element in the electrode material. Figure 5 And as shown in Table 1.

[0109] Table 1 Chemical composition of FCC phase and Mo2C phase in HEA analyzed by EDX (%)

[0110]

[0111] The results show that Fe, Co and Ni elements are evenly distributed on the surface of the material, indicating that the electrode material prepared in Example 2 has a uniform matrix; Mo and C elements are gathered together, indicating that the electrode material prepared in Example 2 contains a precipitation phase with carbon and molybdenum as the main elements; the uniform matrix mainly contains Fe, Co and Ni elements, accounting for 29.93%, 13.19% and 51.89% respectively, while the content of Mo and C elements is relatively small. The Mo2C precipitation phase is mainly composed of Mo and C elements, accounting for 79.43% and 16.15% respectively, which is consistent with the 2:1 atomic ratio composition of Mo2C. It shows that the electrode material prepared in Example 2 is composed of Fe and Ni elements as the matrix, and Mo and C elements are precipitated between the matrix in the form of 2:1 compounds.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode, characterized in that: The following steps are involved: (1) Four metal powders of Fe, Co, Ni and Mo are mixed with carbon powder, ball milled, and allowed to stand for passivation to obtain a mixed powder; (2) Pressing the mixed powder obtained in step (1) into a shape and sintering the mixture to obtain a product.

2. The method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 1, characterized in that: In the step (1), the atomic percentages of the four metal powders of Fe, Co, Ni and Mo are: Fe 10-20%, Co 25-28%, Ni 35-45% and Mo 20-22%; and the particle size of the four metal powders is 60-65 μm.

3. The method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 2, characterized in that: The atomic percentages of the four metal powders of Fe, Co, Ni and Mo are: Fe 10%, Co 25%, Ni 45% and Mo 20%.

4. The method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 1, characterized in that: In the step (1), the mass ratio of the total mass of the four metal powders to the carbon powder is (50-70):(0.05-0.2), and the particle size of the carbon powder is 60-65 μm.

5. The method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 1, characterized in that: The ball milling conditions in step (1) are as follows: the ball-to-material mass ratio is (5-20): (0.8-1.2), and stearic acid is added in an amount of 0.8-1.2% of the total mass of the four metal powders; the mixture is pre-mixed at a speed of 230-270 rpm for 5-7 hours, and then mechanically alloyed and mixed at a speed of 280-320 rpm for 80-90 hours; and the mechanical alloying mixing is performed by interval ball milling, with each ball milling for 40-60 minutes and an interval of 5-15 minutes.

6. The method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 1, characterized in that: The static passivation time in step (1) is 40-60 hours.

7. The method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 1, characterized in that: The conditions for the compression molding in step (2) are: firstly, a disc-shaped green body is obtained by compression in a mold, and then a single-sided pressure of 5-7 MPa is applied for 5-20 minutes; the diameter of the disc-shaped green body is 5-20 mm, and the thickness is 1-3 mm.

8. The method for preparing a carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 1, characterized in that: The sintering conditions in step (2) are as follows: in a protective gas atmosphere, firstly heating the temperature to 200-250°C at a heating rate of 8-12°C / min and keeping the temperature for 40-80min, then heating the temperature to 1050-1150°C at a heating rate of 4-6°C / min and keeping the temperature for 40-80min.

9. A carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. Use of the carbon-doped non-precious metal high entropy alloy hydrogen evolution catalytic electrode according to claim 9 in hydrogen production by electrolysis.

Citation Information

Patent Citations

  • Porous hydrogen evolution catalyst, preparation method of porous hydrogen evolution catalyst and electrode containing hydrogen evolution catalyst

    CN105483744A

  • Preparation method of phosphorus-doped hydrogen evolution catalytic electrode

    CN117552031A

Cited By

  • Preparation method of manganese-doped nickel sulfide / porous foamed nickel electrode for bifunctional alkaline electrolytic water

    CN120138693A

  • A preparation method of a bifunctional alkaline electrolytic water manganese-doped nickel sulfide / porous nickel foam electrode

    CN120138693B